Hip Osteoarthritis: Etiopathogenesis and Implications for Management. Issue 11 (November 2016) - Murphy, Nicholas; Eyles, Jillian; Hunter, David
Abstract Highly prevalent among the elderly, hip osteoarthritis (OA) carries a heavy burden of disease. Guidelines for the management of hip OA are often extrapolated from knee OA research, despite clear differences in the etiopathogenesis and response to treatments of OA at these sites. We propose that hip OA requires specific attention separate from other OA phenotypes. Our understanding of the etiopathogenesis of hip OA has seen significant advance over the last 15 years, since Ganz and colleagues proposed femoroacetabular impingement (FAI) as an important etiological factor. This narrative review summarizes the current understanding of the etiopathogenesis of hip OA and identifies areas requiring further research. Therapeutic approaches for hip OA are considered in light of the condition's etiopathogenesis. The evidence for currently adopted management strategies is considered, especially those approaches that may have disease-modifying potential. We propose that shifting the focus of hip OA research and public health intervention to primary prevention and early detection may greatly improve the current management paradigm.